2010
DOI: 10.1111/j.1365-3024.2010.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in immune parameters are associated with resistance to Haemonchus contortus in Caribbean hair sheep

Abstract: Caribbean hair sheep are more resistant to gastrointestinal nematodes than conventional wool breeds, but mechanisms that confer resistance are not fully understood. This study compared immune effector cell populations and antibody concentrations in 12 hair and 12 wool lambs infected with the abomasal parasite Haemonchus contortus and sacrificed at 3 or 27 days post-infection (p.i.) and 14 uninfected animals of each breed. Faecal egg counts were over 2.5-fold higher (P = 0.12) and packed cell volumes approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 55 publications
3
38
1
1
Order By: Relevance
“…This result suggested that exposure to L 3 larvae of H. contortus triggered an acquired immune response that may have impacted both newly acquired larvae and adult worms. Support for this hypothesis is provided by results of MacKinnon et al (2010MacKinnon et al ( , 2015 and Jacobs et al (2016), who documented that a secondary exposure of St. Croix lambs to L 3 larvae of H. contortus initiated a cascade of protective immune responses within 3 days of infection.…”
Section: Discussionmentioning
confidence: 72%
“…This result suggested that exposure to L 3 larvae of H. contortus triggered an acquired immune response that may have impacted both newly acquired larvae and adult worms. Support for this hypothesis is provided by results of MacKinnon et al (2010MacKinnon et al ( , 2015 and Jacobs et al (2016), who documented that a secondary exposure of St. Croix lambs to L 3 larvae of H. contortus initiated a cascade of protective immune responses within 3 days of infection.…”
Section: Discussionmentioning
confidence: 72%
“…St. Croix (STC) hair sheep demonstrate a remarkable ability to clear a parasitic infection of Haemonchus contortus without anthelmintic drug treatment and, therefore, are considered parasite‐resistant . These sheep are not considered desirable commercial sheep due to low carcass weights and slow growth rates compared to conventional wool breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Host immunity against helminth infections is dependent on innate and acquired immune responses (STEAR & WAKELIN, 1998) and the interaction of these responses confers protection by inducing eosinophilic inflammation, mastocytosis and activation of Th2 responses, with increased expression of interleukin (IL) -4, IL-5 and IL-13 in target tissues and production of IgE and IgA (MACKINNON et al, 2009(MACKINNON et al, , 2010. In contrast, animals susceptible to infection develop Th1 responses, with secretion of cytokines such as IL-2, interferon-gamma (IFNG) and tumor necrosis factor (GILL et al, 2000).…”
Section: Introductionmentioning
confidence: 99%